PENGELOLAAN SAMPAH MENJADI ENERGI BERBASIS TEMPAT OLAH SAMPAH SETEMPAT (TOSS) DI KOTA TANGERANG SELATAN - Iyus Hendrawan; Mohamad Haifan (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
One of the serious problems faced by the South Tangerang City Government today is waste management. According to the Tangsel City DKPP, the volume of waste is 800 tons or around 3,600 cubic meters per day. Until now, the community's waste management system is carried out with a 3R (Reduce-Reuse-Recycle) system in 49 TPS-3Rs that are spread out in every district in the South Tangerang area. The problem at this time is that some of the TPS-3R have not yet operated optimally, so the volume of waste transported to the Cipeacang TPA is still high. Management of waste into energy based on Local Waste Management Sites (TOSS) through a collaboration between STT-PLN and ITI was developed to process waste that produces pellets as an energy raw material that can be used for cooking (special stoves), processing it in a gasifier machine to get gas (syngas) ) which can be consumed by household or electricity generator raw materials. At present trials of the application of TOSS are conducted in several TPS-3Rs in Setu and Pamulang Districts. The series of activities carried out include training and mentoring processing of waste (various types of waste) into pellets, design, manufacture and testing of pellet-fueled stoves, as well as the design, manufacture and testing of gasifier machines to produce gas (syngas) which is distributed to households. The implementation of a TOSS-based waste management system is expected to be able to solve the waste problem in South Tangerang City and get added value through the conversion of waste into energy that can be utilized by the community.Keywords: garbage, TPS-3R, local waste management (TOSS), waste pellets, South Tangerang City